2017
DOI: 10.1101/133801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissociable neural information dynamics of perceptual integration and differentiation during bistable perception

Abstract: At any given moment, we experience a perceptual scene as a single whole and yet we may

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 68 publications
(76 reference statements)
3
19
0
Order By: Relevance
“…On the other hand, before the percept was reported as differentiated (two stimuli, each moving sideways in a different direction), we observed higher information differentiation of anterior signals, but not posterior signals, before the perceptual switch indicated by the button press. These results indicate that our information based measures derived from electrophysiological activity capture and track the phenomenology of the dominant percept during perceptual ambiguity (see also for (28). When perceptual changes were inferred from eye-movements during passive viewing, we observed that when percepts changed from differentiated to integrated, we still observed increased integration in the brain, uniquely in the feedback direction (from anterior to posterior signals).…”
Section: Discussionsupporting
confidence: 67%
“…On the other hand, before the percept was reported as differentiated (two stimuli, each moving sideways in a different direction), we observed higher information differentiation of anterior signals, but not posterior signals, before the perceptual switch indicated by the button press. These results indicate that our information based measures derived from electrophysiological activity capture and track the phenomenology of the dominant percept during perceptual ambiguity (see also for (28). When perceptual changes were inferred from eye-movements during passive viewing, we observed that when percepts changed from differentiated to integrated, we still observed increased integration in the brain, uniquely in the feedback direction (from anterior to posterior signals).…”
Section: Discussionsupporting
confidence: 67%
“…First, a neural measure of information sharing could in principle capture directly the information integration between stimulus content and stimulus location necessary for generating the conflict effect in our task. Second, the dynamic nature of neural information integration (Imperatori et al, 2019;Canales-Johnson et al, 2020) may be able to capture the reconfiguration of neural networks during the transition from an alert to a drowsy state of mind. Finally, as the reorganization of networks could be reflected in the need for larger information capacity of the brain when challenged (by drowsiness), the measure chosen can be conceptually framed as deriving from a computational principle.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that the neural signatures of conflict may involve changes in connectivity in a wide network of brain regions instead of relatively local power changes. Thus, we hypothesized that a neural metric specifically indexing distributed neural information integration (weighted Symbolic Mutual Information (wSMI); King et al, 2013;Sitt et al, 2014;Imperatori et al, 2019;Canales-Johnson et al, 2020) could in principle capture the conflict effect during drowsiness. wSMI has been shown to capture network reconfiguration both in healthy (Imperatori et al, 2019) and pathological (King et al, 2013;Sitt et al, 2014) states of alertness.…”
Section: Distributed Theta-band Information Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of applying algorithmic complexity to EEG signals has been successfully employed to discriminate between states of consciousness (83)(84)(85)(86). One such algorithmic complexity is the Kolmogorov Complexity (K-complexity), which can be described as the ultimate compressed version or minimum description length of an object, delivering its absolute information content (87).…”
Section: Information Distancementioning
confidence: 99%